Pengaruh Desain Produk, Word Of Mouth, dan Kualitas Informasi Terhadap Keputusan Pembelian Rumah PT Ciptatama Griya Prima - Feby Permata Sari; Inda Sukati (eCo-Buss, 2023)
The purpose of this study is to determine the effect of product design, word of mouth, and information quality on the decision to purchase house at PT Ciptatama Griya Prima. The sample in this study were customers' of PT Ciptatama Griya Prima, in Batam, Sagulung sub-district and Batam City, totaling 100 respondents with one-sample kolmogorov-smirnov method.The results indicated that product design, word of mouth and information quality have a positive effect on purchase decision with the regression equation Y = 9,131 + 0,058X1 + 0,140X2 + 0,812X3 + e. The contribution of the influence of product design, word of mouth and information quality to purchase decision simultaneously is 53.7%, the calculated F value is greater than F table or (39.356 > 2.70) with a significance of 0.000 < 0.05. There is a simultaneous positive and significant effect among independent and dependent variable